1950
DOI: 10.5254/1.3547003
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Studies of 1,2- and Trans 1,4-Structure of Polybutadiene and Butadiene-Styrene Copolymers Polymerized at Various Temperatures

Abstract: Infrared methods have been used in determining 1,2- and trans-1,4-addition in polybutadiene polymerized in the temperature range −19° to 97° and butadiene-styrene copolymers prepared at −18°, 5° and 50°. trans-1,4-Addition increases and 1,2-addition decreases with decreasing temperature of polymerization. At −19°, substantially all of the 1,4-addition product is present in the trans-1,4-form. Approximately 20 per cent 1,2-addition occurs at this temperature and is concluded to account for the major part of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1954
1954
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…36,37 The peak at 960 cm À1 , in particular, can correspond to either the trans-1,4 or cis-1,4 isomer since they are difficult to distinguish. 31 Vibrations from out-ofplane ]CH wagging (due to 1,2 addition during polymerization 38 ), C]C stretching and ]CH stretching in B are responsible for the peaks positioned at 913, 1641 and 3003 cm À1 , respectively. Lastly, a doublet located at 2920 and 2832 cm À1 is a result of CH 2 antisymmetric and symmetric stretching in the B repeat units.…”
Section: Analysis Of Sulfonation Reactionmentioning
confidence: 99%
“…36,37 The peak at 960 cm À1 , in particular, can correspond to either the trans-1,4 or cis-1,4 isomer since they are difficult to distinguish. 31 Vibrations from out-ofplane ]CH wagging (due to 1,2 addition during polymerization 38 ), C]C stretching and ]CH stretching in B are responsible for the peaks positioned at 913, 1641 and 3003 cm À1 , respectively. Lastly, a doublet located at 2920 and 2832 cm À1 is a result of CH 2 antisymmetric and symmetric stretching in the B repeat units.…”
Section: Analysis Of Sulfonation Reactionmentioning
confidence: 99%
“…The microstructure of copolymers can be affected by factors such as the polymerization system, reaction conditions, and monomer characteristics (solubility, reactivity ratios, monomer/water and comonomer ratio). The microstructure of poly(styrene‐ co ‐butadiene) (SBR) copolymers has been studied using IR,1, 2 NMR,3 and other techniques 4. It was found that, for the conventional emulsion polymerization of SBR, the initiator, surfactant, and chain transfer agent have little or no effect on the microstructure of the resulting emulsion polymers.…”
Section: Introductionmentioning
confidence: 99%